Local Health Department Epidemiologic Capacity: A Stratified Cross-Sectional Assessment Describing the Quantity, Education, Training, and Perceived Competencies of Epidemiologic Staff - O'Keefe, Kaitlin A.; Shafir, Shira C.; Shoaf, Kimberley I. (Frontiers in Public Health, 2013)
Introduction: Local health departments (LHDs) must have sufficient numbers of staff functioning in an epidemiologic role with proper education, training and skills to protect the health of communities they serve. This pilot study was designed to describe the composition, training and competency level of LHD staff and examine the hypothesis that potential disparities exist between LHDs serving different sized populations. Material and Methods: Cross-sectional surveys were conducted with directors and epidemiologic staff from a sample of 100 LHDs serving jurisdictions of varied sizes. Questionnaires included inquiries regarding staff composition, education, training and measures of competency modeled on previously conducted studies by the Council of State and Territorial Epidemiologists. Number of epidemiologic staff, academic degree distribution, epidemiologic training and both director and staff confidence in task competencies were calculated for each LHD size strata. Results: Disparities in measurements were observed in LHDs serving different sized populations. LHDs serving small populations reported a smaller average number of epidemiologic staff than those serving larger jurisdictions. As size of population served increased, percentages of staff and directors holding bachelors’ and masters’ degrees increased, while those holding RN degrees decreased. A higher degree of perceived competency of staff in most task categories was reported in LHDs serving larger populations. Discussion: LHDs serving smaller populations reported fewer epidemiologic staff, therefore might benefit from additional resources. Differences observed in staff education, training and competencies suggest that enhanced epidemiologic training might be particularly needed in LHDs serving smaller populations. Results can be used as a baseline for future research aimed at identifying areas where training and personnel resources might be particularly needed to increase the capabilities of LHDs.